The eternal city : poems - Graber, Kathleen (Princeton series of contemporary poets., 2010)
Chosen by Pulitzer Prize-winning poet Paul Muldoon to relaunch the prestigious Princeton Series of Contemporary Poets under his editorship, The Eternal City revives Princeton's tradition of publishing some of today's best poetry. With an epigraph from Freud comparing the mind to a landscape in which all that ever was still persists, The Eternal City offers eloquent testimony to the struggle to make sense of the present through conversation with the past. Questioning what it means to possess and to be possessed by objects and technologies, Kathleen Graber's collection brings together the elevated and the quotidian to make neighbors of Marcus Aurelius, Klaus Kinski, Walter Benjamin, and Johnny Depp. Like Aeneas who escapes Troy carrying his father on his back, the speaker of these intellectually and emotionally ambitious poems juggles the weight of private and public history as she is transformed from settled resident to pilgrim.